1991
DOI: 10.1016/0304-3959(91)90216-k
|View full text |Cite
|
Sign up to set email alerts
|

Coping with chronic pain: a critical review of the literature

Abstract: A growing number of investigators have used models of stress and coping to help explain the differences in adjustment found among persons who experience chronic pain. This article reviews the empirical research which has examined the relationships among beliefs, coping, and adjustment to chronic pain. Although preliminary, some consistent findings are beginning to emerge. For example, patients who believe they can control their pain, who avoid catastrophizing about their condition, and who believe they are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
357
4
16

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(400 citation statements)
references
References 85 publications
23
357
4
16
Order By: Relevance
“…Such items appear to assess emotional responses (in fact, resemble items on the Beck Depression Inventory), rather than efforts to deal with the stressor. Jensen et al (29) and Sullivan and D'Eon (30) discuss this issue and provide evidence supporting both sides: Items on the CSQ have been rated as representing symptoms of depression (30), and longitudinal studies have suggested that initial catastrophization scores predict later depression, even when initial depression scores are controlled for (22). Thus, conclusions about cognitive coping and psychological outcome should be made with caution.…”
Section: Issues Of Methodology and Theorymentioning
confidence: 99%
“…Such items appear to assess emotional responses (in fact, resemble items on the Beck Depression Inventory), rather than efforts to deal with the stressor. Jensen et al (29) and Sullivan and D'Eon (30) discuss this issue and provide evidence supporting both sides: Items on the CSQ have been rated as representing symptoms of depression (30), and longitudinal studies have suggested that initial catastrophization scores predict later depression, even when initial depression scores are controlled for (22). Thus, conclusions about cognitive coping and psychological outcome should be made with caution.…”
Section: Issues Of Methodology and Theorymentioning
confidence: 99%
“…Both psychological and psychosocial interventions in addition to conventional exercise therapy may have a more positive effect on treatment outcome [80][81][82][83][84][85][86][87][88][89][90]. The targeted effect of such an approach would be the development of a sense of control over pain and the elimination of pain-avoidance mechanisms, whilst simultaneously improving overall physical fitness/function.…”
Section: Future Thoughtsmentioning
confidence: 99%
“…However, it is possible that important aspects of coping are not tapped by the pain coping measure employed here, for the HPCQ is based on the Coping Strategies Questionnaire [33], and there are measures that include other aspects of pain coping [17,32]. It may also be that active coping per se may not be important or relevant in hemophilia.…”
Section: High Negative Thoughtsmentioning
confidence: 99%
“…Pain coping usually refers to purposeful efforts, including both active and passive strategies, to manage pain or reduce its impact, irrespective of whether those efforts are successful [16,17,44]. Pain coping inventories sometimes also include negative thoughts about pain, such as fear, anger and catastrophizing [12,33], which probably reflect emotional distress associated with pain rather than efforts at coping [13,43,44].…”
Section: Introductionmentioning
confidence: 99%